Experimental and numerical thermal analysis for direct microwave heating of silicon carbide. Issue 1 (14th September 2020) - Ghorbel, Inès; Ganster, Patrick; Moulin, Nicolas; Meunier, Christophe; Bruchon, Julien
Abstract: A comparison between experiment and numerical simulation of microwave heating of a parallelepipedic silicon carbide (SiC) sample is presented. Using a‐2.45 GHz single‐mode cavity, the evolution of the surface temperature is first experimentally studied for different orientations of the sample. A finite element analysis of this electromagnetic‐thermal coupled problem is then conducted with the COMSOL Multiphysics ® software. Despite the different approximations of our model, a good agreement between experimental and numerical results is found, confirming that the heating of SiC depends only on the electric field. The effect of sample orientations and the cavity length on heating is also highlighted and analyzed.